The Coronal Flap in Oral and Maxillofacial Surgery - A Case Report - A.O. Oyeneyin; O. Bankole; M. Asha; A.T. Amoo; E.I. Anorue; C.O. Olojede; G.T. Arotiba (Nigerian Dental Association, 2020)
The coronal scalp flap is a versatile and aesthetically pleasing approach for access to the cranial vault, cranial base, forehead, nose, upper and  middle third of the face, and orbits. In spite of its extensive nature, it is associated with few complications when properly planned. Despite, its versatility of the coronal flap, its use by oral and maxillofacial surgeons is limited especially in Nigeria. A case of surgical remodeling of fibrous dysplasia of the right supra orbital bone region using coronal approach is reported. This article highlighted surgical technique of coronal flap and indications for the use of coronal flap in maxillofacial surgery. Similarly, possible complications of the procedure, prevention and management of such complications were also emphasised. Additionally, it is meant to serve as a guide to young practising surgeons in Nigeria. It is our hope that this will embolden young surgeons in Nigeria to employ its use when indicated.